Analysis of Science Literacy Ability of Junior High School Students with the NOSLiT Method of South Konawe Regency - Syarifuddin Syarifuddin; Hasnawati Hasnawati; Ordiman Lasaima; Muh. Safiuddin Saranani (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Scientific literacy is seen not only as an important component of science education, but also as an ethical/moral competency. Science education plays an important role in creating responsible citizens, in this case scientific literacy is needed in making social-scientific decisions. Currently the concept of scientific literacy is a learning goal in the educational curriculum in various countries. Scientific literacy emphasizes students to analyze, predict, and apply scientific concepts in everyday life. Likewise with students in South Konawe district for the junior high school level, the majority of whose scientific literacy results are classified as lacking. Therefore, this research focuses on the Analysis of Science Literacy Ability of Junior High School Students Using the Nature of Science Literacy Test (NOSLiT) Method in Konawe Selatan Regency. The research method used in this research is quantitative with a descriptive approach. The sampling technique in this study used a simple random sampling technique. The result is that the scientific literacy skills of SMPN Konawe Selatan students based on the NOSLiT instrument in class IX are still in the low category while those in class VII and class VIII are classified as very low. This can be seen from the acquisition of the overall average NOSLiT score for all grade levels, namely 37%, 39.4% and 45.5% respectively, and after calculating the overall score, the average percentage of scientific literacy ability of Konawe Middle School students is obtained. South is in the low category of 40.8%. The achievement of scientific literacy for the NOSLiT indicator of SMPN Konawe Selatan students at all grade levels obtained the highest percentage of achievement in the scientific naming aspect, followed by the scientific misconception aspect, and the ability to process skills and the lowest percentage of achievement lies in the aspect of science postulates. In general, the highest achievement for all NOSLiT indicators was obtained by class IX, followed by class VIII and class VII. The percentage achievement for class IX for indicators of scientific naming, process skills ability, and major misconceptions reached 50% and was above 50% but still this percentage is still in the low category.